Y-type hexagonal ferrite, and manufacturing method and application thereof

By developing a composite material of Co2Y type hexagonal ferrite and polymer, the problem of high magnetic loss in existing ferrite in high-frequency applications is solved, and low loss and high magnetic permeability are achieved in the frequency range of 1GHz to 2GHz. Performance, suitable for compact size antenna components.

CN119325633APending Publication Date: 2025-01-17ROGERS CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380045441.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-08
Filing Date
2023-06-02
Publication Date
2025-01-17

Smart Images

  • Figure CN119325633A_ABST
    Figure CN119325633A_ABST
Patent Text Reader

Abstract

In one aspect, the Co2Y-type ferrite comprises an oxide of at least Ba, La, Co, Me, Fe, and optionally Ca; wherein Me is at least Ni and optionally one or more of Zn, Cu, Mn, or Mg. The composite material may include a Co2Y-type ferrite and a polymer. An article may include a Co2Y-type ferrite.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Application Serial No. 63 / 350,248, filed on June 8, 2022, which is incorporated herein by reference in its entirety. Background Art

[0003] The present disclosure relates to Y-type hexagonal ferrites comprising lanthanum and nickel.

[0004] Improved performance and miniaturization are needed to meet the growing demand for devices used in very high frequency applications, which is of particular concern in various commercial and defense-related industries. Antenna elements with compact size are being developed as important components in radar and global positioning system (GPS) navigation systems. However, the development of ferrite materials for such high frequency applications is challenging because most ferrite materials exhibit relatively high magnetic losses at high frequencies.

[0005] Generally, hexagonal ferrite or hexaferrite is a type of iron oxide ceramic composite having a hexagonal crystal structure and exhibiting magnetic properties. Several types of hexagonal ferrite families are known, including Z-type ferrite Ba3Me2Fe 24 O 41 and Y-type ferrite Ba2Me2Fe 12 O 22 , where Me can be a small 2+ cation such as Co or Zn, and Sr can replace Ba. Other hexagonal ferrite types include M-type ferrites ((Ba,Sr)Fe 12 O 19 )、W-type ferrite ((Ba,Sr)Me2Fe 16 O 27 ), X-type ferrite ((Ba,Sr)2Me2Fe 28 O 46 ) and U-type ferrite ((Ba,Sr)4Me2Fe 36 O 60 ).

[0006] Hexagonal ferrites with high magnetocrystalline anisotropy fields are good candidates for gigahertz antenna substrates because they have high magnetocrystalline anisotropy fields and thus high ferromagnetic resonance frequencies. Despite having low loss values ​​of about one gigahertz, improved ferrites are still desired. Summary of the invention

[0007] This article discloses Co2Y-type hexagonal ferrite.

[0008] In one aspect, the Co2Y-type ferrite comprises oxides of at least Ba, La, Co, Me, Fe, and optionally Ca; wherein Me is at least Ni and optionally one or more of Zn, Cu, Mn, or Mg.

[0009] In another aspect, a composite material comprises a Co2Y-type ferrite and a polymer.

[0010] In yet another aspect, the article may include Co2Y-type ferrite.

[0011] In another aspect, a method of making Co2Y type ferrite includes grinding a ferrite precursor compound including oxides of at least Ba, La, Co, Me and Fe to form a magnetic oxide mixture, wherein Me includes Ni and optionally another divalent element, such as one or more of Zn, Cu, Mn or Mg; and calcining the magnetic oxide mixture in an oxygen or air atmosphere to form Co2Y type ferrite.

[0012] The above described features and further features are exemplified by the detailed description and claims. DETAILED DESCRIPTION

[0013] It is found that Co2Y-type ferrites containing both lanthanum and nickel show very low losses in the frequency range of 1 gigahertz (GHz) to 2 GHz, which is difficult to achieve with Y-type ferrites. For example, it is found that the specific magnetic loss of Co2Y-type ferrites in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz can be less than or equal to 0.02, or less than or equal to 0.03, or less than or equal to 0.015, or 0.012 to 0.03. Co2Y-type ferrites contain oxides of at least Ba, La, Co, Me, Fe, and optionally Ca; wherein Me is at least Ni and optionally one or more of Zn, Cu, Mn, or Mg. Co2Y-type ferrites may have formula (1) or formula (2).

[0014] Ba 1-x La x Ca n Co 2-y-z Me y Fe 12-m O 22 (1)

[0015] Ba 1-x La x Ca n Co 2-y-z Ni y Fe 12-m O 22 (2)

[0016] Me includes Ni and optionally one or more of Zn, Cu, Mn or Mg. The variable x may be from 0.01 to 0.5, or from 0.4 to 0.5. The variable y may be from 0.01 to 1.5, or from 0.1 to 1, or from 0.2 to 0.5. The variable z may be from -0.5 to 0.5, or from -0.2 to 0. The variable m may be from -2 to 2, or from 0.1 to 0.5. The variable n may be from 0 to 0.5.

[0017] The Co2Y type ferrite may be in the form of particles (eg, having a spherical shape or an irregular shape) or in the form of platelets, whiskers, flakes, etc. The D of the granular Co2Y type ferrite by volume is 50 The particle size can be 0.5 micron to 50 microns, or 0.5 micron to 20 microns, or 1 micron to 10 microns, or 0.1 micron to 1 micron. The average particle size of the Co2Y type ferrite as measured using scanning electron microscopy can be 0.5 micron to 50 microns, or 0.5 micron to 20 microns, or 1 micron to 10 microns. The small pieces of the Co2Y type ferrite can have an average maximum length of 0.1 micron to 100 microns and an average thickness of 0.05 microns to 1 micron. Based on the total volume of the Co2Y type ferrite, the porosity of the Co2Y type ferrite can be 0 volume percent (volume %) to 50 volume percent, or 20 volume percent to 45 volume percent.

[0018] Co2Y type ferrite can be formed by mixing precursor compounds including oxides of at least Ba, La, Co, Me, Fe and optionally Ca to form a magnetic oxide mixture (wherein Me includes Ni and optionally another divalent element, such as one or more of Zn, Cu, Mn or Mg), and calcining the magnetic oxide mixture in an oxygen or air atmosphere to form Co2Y type ferrite. The resulting Co2Y type ferrite may have formula (1) or formula (2). Examples of oxides may include BaCO3, CaCO3, Co3O4, Fe2O3, La2O3, NiO, MgO, ZnO and CuO.

[0019] The Co2Y type ferrite can be calcined. Calcination can be carried out at a calcination temperature of 800°C to 1,300°C, or 800°C to 1,280°C, or 900°C to 1,250°C. Calcination can be carried out for a calcination time of 0.5 hours to 20 hours, or 1 hour to 10 hours. The heating rate of the calcination step is not particularly limited, and can be carried out at a heating rate and cooling rate of 1 degree Celsius per minute (°C / min) to 5°C / min, or 2°C / min to 4°C / min. Calcination can be carried out in air or in an oxygen environment, for example, under an oxygen flow with a flow rate of 0.1 liters / min to 10 liters / min. The calcination step can be the only heating step used when manufacturing the Co2Y type ferrite.

[0020] After the calcining step, the calcined ferrite may be ground and sieved to form coarse particles. The coarse particles may be ground into D 50 The particle size is 0.1 micron to 20 microns, or 0.5 micron to 20 microns, or 1 micron to 10 microns, or 0.1 micron to 1 micron.

[0021] The Co2Y type ferrite can be ground. The grinding can be carried out for a grinding time greater than or equal to 1 minute to 10 minutes, or 5 minutes to 60 minutes, or 1 minute to 10 hours. The grinding can be carried out at a mixing speed greater than or equal to 300 revolutions per minute (rpm), or 300rpm to 1,000rpm, or less than or equal to 600rpm, or 400rpm to 500rpm. The grinding can be carried out in a wet planetary ball mill. The ground mixture can be optionally sieved, for example, using a 10# to 300# sieve. The ground mixture can be mixed with a polymer such as poly (vinyl alcohol) to form a pellet. The average D by volume of the pellet is 50 The particle size can be 50 microns to 300 microns. The ground mixture can be formed or shaped, for example, by pressing at a pressure of 0.2 megatons / cm2 to 2 megatons / cm2. The ground mixture (granular or shaped) can be heated at a temperature of 50°C to 500°C, 200°C to 1,280°C, or 100°C to 250°C. The ground mixture (granular or shaped) can be post-annealed at an annealing temperature of 900°C to 1,275°C, or 1,200°C to 1,250°C. Heating or annealing can be performed for 1 hour to 20 hours, or 4 hours to 6 hours, or 5 hours to 12 hours. Annealing can be performed in air or oxygen.

[0022] The Co2Y ferrite may include a surface coating. The coating may allow the amount of Co2Y ferrite in the composite material to be increased. The coating may be a hydrophobic coating. The coating may include at least one of a silane coating, a titanate coating, or a zirconate coating.

[0023] The silane coating may be formed from a silane, which may include at least one of a linear silane, a branched silane, or a cyclic silane. The silane may include a precipitated silane. The silane may be free of a solvent (e.g., toluene) or a dispersed silane, such as a solvent dispersed silane containing 0 weight percent (wt%) to 2 weight percent (e.g., 0 weight percent) based on the total weight of the silane.

[0024] A variety of different silanes can be used to form the coating, including one or both of phenylsilane and fluorosilane. The phenylsilane can be p-chloromethylphenyltrimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, phenyltrichlorosilane, phenyl-tri-(4-biphenyl)silane, hexaphenyldisilane, tetra-(4-biphenyl)silane, tetra-Z-thienylsilane, phenyltri-Z-thienylsilane, 3-pyridyltriphenylsilane, or a combination comprising at least one of the foregoing. Functionalized phenylsilanes as described in US 4,756,971 can also be used, for example, formula R'SiZ 1 R 2 Z 2 A functionalized phenylsilane wherein R' is an alkyl group having 1 to 3 carbon atoms, -SH, -CN, -N3 or hydrogen; Z 1 and Z 2 are each independently chlorine, fluorine, bromine, an alkoxy group having no more than 6 carbon atoms, NH, -NH2, -NR2'; and R 2 for

[0025]

[0026] wherein the S substituents S1, S2, S3, S4 and S5 are each independently hydrogen, an alkyl group having 1 to 4 carbon atoms, a methoxy group, an ethoxy group or a cyano group, provided that at least one of the S substituents is not hydrogen, and when a methyl S substituent or a methoxy S substituent is present, then (i) at least two of the S substituents are not hydrogen, (ii) two adjacent S substituents form a naphthyl or anthracenyl group with the phenyl core, or (iii) three adjacent S substituents form a pyrenyl group with the phenyl core, and X is a group -(CH2) n -, wherein n is 0 to 20, particularly when n is not 0, n is 10 to 16, in other words, X is an optional spacer group, S is a substituent. The term "lower" with respect to a group or compound means 1 to 7, or 1 to 4 carbon atoms.

[0027] The fluorosilane coating may be made of a material having the formula CF3(CF2) n-CH2CH2SiX is formed by a perfluorinated alkylsilane, wherein X is a hydrolyzable functional group, and n=0 or all integers. Fluorosilanes may include at least one of the following: (3,3,3-trifluoropropyl)trichlorosilane, (3,3,3-trifluoropropyl)dimethylchlorosilane, (3,3,3-trifluoropropyl)methyldichlorosilane, (3,3,3-trifluoropropyl)methyldimethoxysilane, (tridecafluoro-1,1,2,2-tetrahydrooctyl)-1-trichlorosilane, (tridecafluoro-1,1,2,2-tetrahydrooctyl)-1-methyldi ... The invention can be any of the following: (heptafluorooctyl)-1-dimethylchlorosilane, (heptadecafluoro-1,1,2,2-tetrahydrodecyl)-1-methyldichlorosilane, (heptadecafluoro-1,1,2,2-tetrahydrodecyl)-1-trichlorosilane, (heptadecafluoro-1,1,2,2-tetrahydrodecyl)-1-dimethylchlorosilane, (heptafluoroisopropoxy)propylmethyldichlorosilane, 3-(heptafluoroisopropoxy)propyltrichlorosilane, 3-(heptafluoroisopropoxy)propyltriethoxysilane, or perfluorooctyltriethoxysilane.

[0028] Other silanes may be used instead of or in addition to phenylsilane or fluorosilane, for example, aminosilanes and silanes containing polymerizable functional groups such as acryl and methacryloyl. Examples of aminosilanes include N-methyl-γ-aminopropyltriethoxysilane, N-ethyl-γ-aminopropyltrimethoxysilane, N-methyl-β-aminoethyltrimethoxysilane, γ-aminopropylmethyldimethoxysilane, N-methyl-γ-aminopropylmethyldimethoxysilane, N-(β-N-methylaminoethyl)-γ-aminopropyltriethoxysilane, N-(γ-aminopropyl)-γ-aminopropylmethyldimethoxysilane, N-(γ-aminopropyl)-N-methyl-γ-aminopropyl methyldimethoxysilane and γ-aminopropylethyldiethoxysilane, aminoethylaminotrimethoxysilane, aminoethylaminopropyltrimethoxysilane, 2-ethylpiperidinyltrimethylsilane, 2-ethylpiperidinylmethylphenylchlorosilane, 2-ethylpiperidinyldimethylhydrosilane, 2-ethylpiperidinyldicyclopentylchlorosilane, (2-ethylpiperidinyl)(5-hexenyl)methylchlorosilane, morpholinovinylmethylchlorosilane, n-methylpiperazinylphenyldichlorosilane, or a combination comprising at least one of the foregoing.

[0029] Silanes containing polymerizable functional groups include those of formula R a x S i b (3-x) R silane, wherein each R a the same or different (eg, the same) and are halogen (eg, Cl or Br), C 1-4 Alkoxy (e.g., methoxy or ethoxy), or C2-6 Acyl; each R b C 1-8 Alkyl or C 6-12 Aryl (e.g., R b may be methyl, ethyl, propyl, butyl or phenyl); x is 1, 2 or 3 (e.g., 2 or 3); and R is -(CH2) n OC(=O)C(R c )=CH2, where R c is hydrogen or methyl, and n is an integer of 1 to 6, or 2 to 4. The silane may include at least one of methacrylsilane (3-methacryloxypropyltrimethoxysilane) or trimethoxyphenylsilane.

[0030] The titanate coating may be formed from: neopentyl(diallyl)oxy, trineodecanoyl titanate; neopentyl(diallyl)oxy, tri(dodecyl)benzenesulfonyl titanate; neopentyl(diallyl)oxy, tri(dioctyl)phosphate titanate; neopentyl(diallyl)oxy, tri(dioctyl)pyrophosphate titanate; neopentyl(diallyl)oxy, tri(N-ethylenediamino)ethyl titanate; neopentyl(diallyl)oxy, tri(m-amino)phenyl titanate; and neopentyl(diallyl)oxy, trihydroxyhexanoyl titanate; or a combination comprising at least one of the foregoing. The zirconate coating may be formed from: neopentyl(diallyloxy)tri(dioctyl)pyrophosphate zirconate, neopentyl(diallyloxy)tri(N-ethylenediamino)ethyl zirconate, or a combination comprising at least one of the foregoing.

[0031] The Co2Y ferrite may be coated to a level of less than or equal to 10 wt%, or less than or equal to 5 wt%, or 0.1 wt% to 5 wt%, or 0.1 wt% to 3 wt%, based on the total weight of the Co2Y ferrite plus coating.

[0032] Co2Y type ferrite particles can be used to make composite materials, such as composite materials comprising Co2Y type ferrite and polymers. Polymers can include thermoplastics or thermosetting plastics. As used herein, the term "thermoplastic" refers to such a material: it is plastic or deformable, melts into a liquid when heated, and freezes into a brittle glass state when fully cooled. Examples of thermoplastic polymers that can be used include cycloolefin polymers (including polynorbornene and copolymers containing norbornene-based units, for example, cyclic polymers such as norbornene and acyclic olefins such as ethylene or propylene copolymers), fluoropolymers (for example, polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), fluorinated ethylene-propylene (FEP), polytetrafluoroethylene (PTFE), poly (ethylene-tetrafluoroethylene (PETFE), or perfluoroalkoxy (PFA)), polyacetals (for example, polyethylene oxide or polyoxymethylene), poly (C 1-6 Alkyl) acrylates, polyacrylamides (including unsubstituted, mono-N- or di-N-(C 1-8 The present invention relates to polyols, for example, polyols (e.g., polyols for example ... azoles, polybenzimidazoles, polycarbonates (including homopolycarbonates or polycarbonate copolymers such as polycarbonate-siloxanes, polycarbonate-esters or polycarbonate-ester-siloxanes), polyesters (e.g., polyethylene terephthalate, polybutylene terephthalate, polyarylates, or polyester copolymers such as polyester-ethers), polyetherimides (e.g., copolymers such as polyetherimide-siloxane copolymers), polyimides (e.g., copolymers such as polyimide-siloxane copolymers), poly(C 1-6 alkyl) methacrylate, polyalkyl acrylamide (e.g., unsubstituted, mono-N- or di-N-(C 1-8 alkyl) acrylamide), polyolefins (e.g., polyethylene such as high-density polyethylene (HDPE), low-density polyethylene (LDPE) or linear low-density polyethylene (LLDPE), polypropylene, or their halogenated derivatives (e.g., polytetrafluoroethylene, or their copolymers (e.g., ethylene-α-olefin copolymers)), poly Oxadiazoles, polyoxymethylenes, polyphthalides, polysilazanes, polysiloxanes (silicones), polystyrenes (e.g., copolymers such as acrylonitrile-butadiene-styrene (ABS) or methyl methacrylate-butadiene-styrene (MBS)), polysulfides, polysulfonamides, polysulfonates, polysulfones, polythioesters, polytriazines, polyureas, polyurethanes, vinyl polymers (e.g., polyvinyl alcohols, polyvinyl esters, polyvinyl ethers, polyvinyl halides (e.g., polyvinyl chloride), polyvinyl ketones, polyvinyl nitrile, or polyvinyl sulfide), paraffin waxes, etc. A combination comprising at least one of the foregoing thermoplastic polymers can be used.

[0033] Thermosetting polymers are derived from thermosetting monomers or prepolymers (resins) that can be irreversibly hardened and rendered insoluble by polymerization or curing, which can be initiated by heat or exposure to radiation (e.g., ultraviolet, visible, infrared, or electron beam (e-beam) radiation). Thermosetting polymers include alkyd resins, bismaleimide polymers, bismaleimide triazine polymers, cyanate polymers, benzocyclobutene polymers, benzophenone azine polymers, diallyl phthalate polymers, epoxy resins, hydroxymethyl furan polymers, melamine-formaldehyde polymers, phenolic resins (including phenol-formaldehyde polymers such as novolacs and resols), benzophenone The prepolymers may be selected from the group consisting of polyimides, polyisocyanates, polyols ... 1-6 alkyl) esters, methacrylate (C 1-6 alkyl) ester, acrylonitrile, vinyl acetate, allyl acetate, triallyl cyanurate, triallyl isocyanurate, or acrylamide.

[0034] The polymer may include at least one of paraffin wax, polytetrafluoroethylene, polyethylene, polypropylene, polyolefin, polyurethane, silicone polymer, liquid crystal polymer, poly(ether ether ketone) or poly(phenylene sulfide) (PPS). The polymer may include a fluorine-containing polymer (e.g., polytetrafluoroethylene (PTFE)). The polymer may include poly(phenylene sulfide).

[0035] If the polymer includes PTFE, powders of PTFE and Co2Y ferrite can be blended together and then air milled. A commercially available example of an air mill is the Jet Pulverizer MICRON-MASTER mill. Air milled powders can allow for higher filler loadings without making the article brittle. Other energy intensive methods can be used, such as blending in a Patterson Kelly V-blender with a reinforcing rod. The thoroughly mixed powder can then be pressed into shape.

[0036] PTFE composites can be prepared by dispersion casting as described in, for example, U.S. Pat. No. 5,506,049 to GSSwei and DJArthur. Dispersion casting can allow the production of PTFE composites filled to more than 60% by volume but still maintaining excellent flexibility. The film can be cast and then sintered on a carrier sheet to produce a free film or the film can be cast onto a glass fabric to form a fabric-reinforced composite sheet. The composite sheet can be used as a dielectric load in a "cast state" or stacked to a desired final thickness and densified in a press. The casting mixture can be made by dispersing the particles in water and combining the slurry with a PTFE dispersion and a stabilizing additive, and increasing the viscosity to keep the particles from settling.

[0037] PTFE composites can be prepared by paste extrusion and calendering to produce flexible particle filled PTFE composites with filler content exceeding 60% by volume. Ferrite fillers can be dispersed in water, mixed with PTFE dispersions, and then co-coagulated with PTFE to form "lumps". As described in GR Traut's U.S. Patent 4,518,787, the lumps can then be lubricated with hydrocarbon liquids and extruded into ribbons that can then be calendered into sheets. Alternatively, fillers and PTFE "fine powders" (also referred to as "coagulated dispersions" PTFE) can be mixed and lubricated in a V-blender, then paste extruded and calendered. Lubricants can be removed, and sheets can be stacked to a desired basis weight and laminated in a flat bed press.

[0038] Based on the total volume of the Co2Y type ferrite composite material, the Co2Y type ferrite composite material can include 5 volume percent to 95 volume percent, or 50 volume percent to 80 volume percent, or 40 volume percent to 60 volume percent of Co2Y type ferrite. Based on the total volume of the Co2Y type ferrite composite material, the Co2Y type ferrite composite material can include 20 volume percent to 50 volume percent of polymer. The Co2Y type ferrite composite material can be formed by compression molding, injection molding, reaction injection molding, lamination, extrusion, calendering, casting, rolling, etc.

[0039] The composite material may have porosity. Based on the total volume of the composite material, the porosity of the composite material may be from 0 volume percent to 45 volume percent, or from 15 volume percent to 35 volume percent. Without intending to be bound by theory, it is believed that the porosity of the composite material may help reduce the dielectric constant of the composite material relative to the magnetic permeability. The porosity may be adjusted by changing one or more of the calcination temperature or the particle size of the ferrite. In contrast, the composite material may have no void space.

[0040] The specific magnetic loss of the Co2Y type ferrite in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz may be less than or equal to 0.02, or less than or equal to 0.03, or less than or equal to 0.015, or 0.012 to 0.03.

[0041] The magnetic permeability (μ') of the Co2Y type ferrite in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz may be greater than or equal to 3, or 3 to 6, or 3 to 4. The magnetic permeability of the composite material in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz may be greater than or equal to 1.5, or 1.5 to 4, or 1.5 to 2.

[0042] The magnetic loss (also called magnetic loss tangent, tanδ) of Co2Y ferrite in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz μ The composite material may have a magnetic loss tangent of less than or equal to 0.1, less than or equal to 0.03, less than or equal to 0.02, or between 0.015 and 0.1 in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz.

[0043] Co2Y type ferrite can have low tanδ μ' / μ' or μ" / μ' 2 For example, Co2Y-type ferrite can have a low specific loss of 0.013 to 0.03 in the frequency range of 1 GHz to 2 GHz.

[0044] The dielectric constant (ε') of Co2Y type ferrite in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz may be less than or equal to 9, or 8 to 13. Depending on the polymer matrix, the dielectric constant of the composite material may be 5 to 8 in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz.

[0045] The dielectric loss (also called dielectric loss tangent, tanδ) of Co2Y ferrite in the frequency range of 1 GHz to 2 GHz or at 1.2 GHzε The dielectric loss of the composite material in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz may be less than or equal to 0.008, or less than or equal to 0.006, or 0.002 to 0.006.

[0046] As used herein, the phrase "at a frequency of..." may mean at a single frequency value within the range or over the entire frequency range. For example, the phrase "the magnetic permeability may be 2 to 10 at a frequency of 0.5 GHz to 3 GHz" may mean that the magnetic permeability is a single value within the range of 2 to 10, such as 3, at a single frequency within the range of 0.5 to 3, such as 1 GHz; or the magnetic permeability may be a value defined by the range of 2 to 10 (e.g., varying with frequency within the range) across the entire frequency range of 0.5 GHz to 3 GHz.

[0047] The magnetic and dielectric properties of ferrite can be measured by a vector network analyzer (VNA) using a coaxial air line in a frequency range of 0.1 GHz to 6 GHz using the Nicholson-Ross-Weir (NRW) method.

[0048] The operating frequency of Co2Y ferrite can be as high as 6 GHz, or 0.5 GHz to 2 GHz.

[0049] The article may include Co2Y ferrite. The article may be, for example, an antenna for GPS tracking. The article may be used in a variety of devices that can operate in the ultra-high frequency range, such as high-frequency or microwave antennas, filters, sensors, circulators, or phase shifters. The article may be an antenna (e.g., a patch antenna), a filter, a sensor, a circulator, or an EMI (electromagnetic interference) suppressor. Such articles may be used in commercial and military applications, weather radar, scientific communications, wireless communications, autonomous vehicles, aircraft communications, space communications, satellite communications, or monitoring.

[0050] The article may include a dielectric layer comprising a composite material; and a conductive layer. Useful conductive layers include, for example, stainless steel, copper, gold, silver, aluminum, zinc, tin, lead, transition metals, and alloys comprising at least one of the foregoing. There is no particular restriction on the thickness of the conductive layer, nor is there any restriction on the shape, size, or surface texture of the conductive layer. The thickness of the conductive layer may be 3 microns to 200 microns, or 9 microns to 180 microns. When there are two or more conductive layers, the thickness of the two layers may be the same or different. The conductive layer may include a copper layer. Suitable conductive layers include thin layers of conductive metals, such as copper foils currently used to form circuits, such as electrodeposited copper foils. The root mean square (RMS) roughness of the copper foil may be less than or equal to 2 microns, specifically less than or equal to 0.7 microns, wherein the roughness is measured using a Veeco Instruments WYCO optical profiler using a white light interferometer method.

[0051] The conductive layer can be applied by placing the conductive layer in a mold prior to molding the composite material, by laminating the conductive layer to the composite material (also referred to herein as a substrate), by direct laser structuring, or by adhering the conductive layer to the substrate via an adhesive layer. Where the specific material and form of the circuit material permit, other methods known in the art may be used to apply the conductive layer, such as electrodeposition, chemical vapor deposition, and the like.

[0052] Lamination may require lamination of a multilayer stack including a substrate, a conductive layer and an optional intermediate layer between the substrate and the conductive layer to form a layered structure. The conductive layer can be in direct contact with the substrate layer without an intermediate layer. The layered structure can then be placed in a press (e.g., a vacuum press) under a certain pressure and temperature and continue to be suitable for combining the layers and forming a laminated body. Lamination and optional curing can be performed by a one-step method, such as using a vacuum press, or can be performed by a multi-step method. In a one-step method, the layered structure can be placed in a press, raised to a lamination pressure (e.g., 150 pounds per square inch (psi) to 400 pounds per square inch (1 megapascal (MPa) to 2.8MPa)) and heated to a lamination temperature (e.g., 260 degrees Celsius (°C) to 390°C). The lamination temperature and pressure can maintain a desired holding time, i.e., 20 minutes, and then cooled (while still under pressure) to less than or equal to 150°C.

[0053] If present, the intermediate layer may include a polyfluorocarbon film that may be positioned between the conductive layer and the substrate layer, and an optional microglass reinforced fluorocarbon polymer layer may be positioned between the polyfluorocarbon film and the conductive layer. The microglass reinforced fluorocarbon polymer layer may improve the adhesion of the conductive layer to the substrate. The microglass may be present in an amount of 4 weight percent (wt%) to 30 weight percent based on the total weight of the layer. The longest length scale of the microglass may be less than or equal to 900 microns, or less than or equal to 500 microns. The microglass may be a type of microglass such as that commercially available through Johns-Manville Corporation of Denver, Colorado. The polyfluorocarbon film comprises a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), a fluorinated ethylene-propylene copolymer (e.g., Teflon FEP), or a copolymer having a tetrafluoroethylene backbone and fully fluorinated alkoxy side chains (e.g., Teflon PFA)).

[0054] The conductive layer can be applied by laser direct structuring. Here, the substrate can include a laser direct structuring additive, and the laser direct structuring can include using a laser to irradiate the surface of the substrate, forming a track of the laser direct structuring additive, and applying a conductive metal to the track. The laser direct structuring additive can include metal oxide particles (such as titanium oxide and copper chromium oxide). The laser direct structuring additive can include inorganic metal oxide particles based on spinel, such as spinel copper. The metal oxide particles can be coated, for example, with a composition comprising tin and antimony (for example, based on the total weight of the coating, 50% to 99% by weight of tin and 1% to 50% by weight of antimony). Based on 100 parts of the corresponding composition, the laser direct structuring additive can include 2 to 20 parts of the additive. Irradiation can be performed with a yttrium aluminum garnet (yttrium aluminum garnet, YAG) laser with a wavelength of 1,064 nanometers at an output power of 10 watts, a frequency of 80 kilohertz (kHz), and a rate of 3 meters per second. A conductive metal can be applied in a chemical plating bath comprising, for example, copper using a plating process.

[0055] Conductive layer can be applied by adhesively applying conductive layer.Conductive layer can be circuit (metallization layer of another circuit), such as flexible circuit.Adhesive layer can be arranged between one or more conductive layers and substrate.When suitable, adhesive layer can comprise at least one of poly (arylene ether) or carboxyl functionalized polybutadiene or polyisoprene polymer, and described carboxyl functionalized polybutadiene or polyisoprene polymer comprises butadiene, isoprene or butadiene and isoprene unit and 0 wt % to 50 wt % co-curable monomer unit.Adhesive layer can exist with the amount of 2 g / m2 to 15 g / m2.Poly (arylene ether) can comprise carboxyl functionalized poly (arylene ether).Poly (arylene ether) can be the reaction product of poly (arylene ether) and cyclic acid anhydride or the reaction product of poly (arylene ether) and maleic anhydride.Carboxyl functionalized polybutadiene or polyisoprene polymer can be carboxyl functionalized butadiene-styrene copolymer. The carboxyl functionalized polybutadiene or polyisoprene polymer may be the reaction product of a polybutadiene or polyisoprene polymer and a cyclic anhydride. The carboxyl functionalized polybutadiene or polyisoprene polymer may be a maleated polybutadiene-styrene or a maleated polyisoprene-styrene copolymer.

[0056] The Co2Y type ferrite may comprise an oxide of at least Ba, La, Co, Me, Fe and optionally Ca; wherein Me is at least Ni and optionally one or more of Zn, Cu, Mn or Mg. The Co2Y type ferrite may have the formula Ba 1-x La x Ca n Co 2-y- z Me y Fe 12-m O 22 , wherein x is 0.01 to 0.5, or 0.1 to 0.5; y is 0.01 to 1.5, or 0.1 to 1, or 0.2 to 0.5; z is -0.5 to 0.5, or -0.2 to 0; and m is -2 to 2, or 0.1 to 0.5; n is 0 to 0.5, or 0.01 to 0.5. Co2Y-type ferrites may have the formula Ba 1-x La x Ca n Co 2-y-z Ni y Fe 12-m O 22 . D of Co2Y type ferrite 50The particle size may be 2 microns to 10 microns. Based on the total volume of the Co2Y ferrite, the porosity of the Co2Y ferrite may be 0 volume percent to 50 volume percent, or 20 volume percent to 45 volume percent. The magnetic permeability of the Co2Y ferrite in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz may be greater than or equal to 3, or 3 to 6, or 3 to 4. The magnetic loss of the Co2Y ferrite in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz may be less than or equal to 0.75, or less than or equal to 0.5, or less than or equal to 0.09, or 0.07 to 0.2. The dielectric constant of the Co2Y ferrite in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz may be less than or equal to 9, or 8 to 9. The dielectric loss of the Co2Y ferrite in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz may be less than or equal to 0.01, or 0.002 to 0.009.

[0057] The composite material comprises a polymer and a Co2Y-type ferrite. The polymer may include at least one of paraffin, polytetrafluoroethylene, polyethylene, polypropylene, polyolefin, polyurethane, silicone polymer, liquid crystal polymer, poly(ether ether ketone) or poly(phenylene sulfide). The polymer may include polytetrafluoroethylene or poly(phenylene sulfide). The magnetic permeability of the composite material in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz may be greater than or equal to 1.5, or 1.5 to 4, or 1.5 to 2. The specific magnetic loss of the composite material in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz may be less than or equal to 0.02, or less than or equal to 0.03, or less than or equal to 0.015, or 0.012 to 0.03. The dielectric constant of the composite material in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz may be less than or equal to 6.5, or 5 to 6.5. The dielectric loss of the composite material in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz may be less than or equal to 0.008, or less than or equal to 0.006, or 0.002 to 0.006. Based on the total volume of the composite material, the composite material may contain 5 volume percent to 95 volume percent, or 50 volume percent to 80 volume percent, or 40 volume percent to 60 volume percent of Co2Y type ferrite. Based on the total volume of the composite material, the porosity of the composite material may be 0 volume percent to 45 volume percent, or 15 volume percent to 35 volume percent.

[0058] The article comprises a ferrite composition or a composite material. The article may be an antenna.

[0059] The method of making Co2Y ferrite may include grinding a ferrite precursor compound including oxides of at least Ba, La, Co, Me and Fe to form a magnetic oxide mixture, wherein Me includes Ni and optionally another divalent element, such as one or more of Zn, Cu, Mn or Mg; and calcining the magnetic oxide mixture in an oxygen or air atmosphere to form Co2Y ferrite. Calcination of the mixed ferrite may be carried out at a calcination temperature of 800°C to 1,300°C, or 900°C to 1,250°C. Calcination of the mixed ferrite may be carried out for a calcination time of 0.5 hours to 20 hours, or 1 hour to 10 hours. The method may also include forming a composite material comprising Co2Y ferrite and a polymer.

[0060] The following examples are provided to illustrate the present disclosure. The examples are illustrative only and are not intended to limit devices made according to the present disclosure to the materials, conditions, or process parameters set forth therein.

[0061] Example

[0062] The magnetic permeability and magnetic loss of ferrite were measured in a coaxial air line by a vector network analyzer (VNA) in the frequency range of 0.1 GHz to 6 GHz using the Nicholson-Ross-Weir (NRW) method.

[0063] The Co2Y-type ferrite preparations used in the examples are listed below as Preparations 1 to 3.

[0064] Preparation I: Ba 1.9 La 0.1 Co 1.6 Zn 0.4 Fe 11.8 O 22

[0065] Preparation II: Ba 1.9 La 0.1 Co 1.4 Ni 0.4 Zn 0.4 Fe 11.7 O 22

[0066] Formulation III: Ba 1.9 La 0.1 Ca 0.1 Co 1.4 Ni 0.4 Zn 0.4 Fe 11.7 O 22

[0067] Examples 1 to 5: Effect of Nickel on the Magnetic Properties of Co2Y Ferrite in Paraffin

[0068] Co2Y ferrite was prepared by mixing BaCO3 (99.9%), CaCO3 (99.5%), Co3O4 (99.9%), La2O3 (99.9%), NiO (99%), ZnO (99.9%) and Fe2O3 (99.4%) in certain amounts to form ferrites of Formulations 1 to 3. The oxide mixture was mixed in a wet planetary ball mill at 350 revolutions per minute (rpm) for two hours, dried in an oven at 100°C, and sieved through a 40# sieve to form coarse particles. The coarse particles were then calcined in air at a temperature of 1,030°C for a holding time of 4 hours to form a ferrite having the formula Ba 0.9 La 0.1 Co 2-x-y-z Ca n Ni x Zn y Fe 12-m O 22 The Co2Y ferrite was then jaw crushed and ground in a planetary ball mill at 350 rpm in a stainless steel tank for 3 minutes, and finally sieved through a 40# sieve and then a 200# sieve. The volume of the ferrite particles was D 50 The particle size is between 2 microns and 6 microns. The Co2Y ferrite is then mixed with paraffin wax to form a composite material comprising 25 volume % to 45 volume % of the Co2Y ferrite.

[0069]

[0070] Table 1 shows that the specific magnetic loss values ​​of Examples 2 to 5 are 0.014 to 0.028, which are lower than the specific magnetic loss value of Example 1 (0.016 to 0.031).

[0071] Examples 6 to 8: Effect of Nickel on the Magnetic Properties of Co2Y Ferrite in PPS

[0072] A 50 cubic centimeter double Banbury rotor mixing bowl is attached to the drive of the Brabender Intelli-TorquePlasti-Corder torque rheometer. The bowl heater is set to a temperature of 315°C. The rotor speed is set to a speed of 75rpm. The mixer body temperature is heated until it reaches a steady state. 29.6 grams (g) of polyphenylene sulfide (PPS) (SOLVAY QA321) and 96.4g of ferrite powder are weighed out respectively. Half of the ferrite is blended with PPS by hand, and the other half is placed aside. The rotor is started, and for the unfilled chamber, the machine calibrates the torque. After calibration, the PPS-ferrite powder is slowly loaded, and the powder is melted into a melt. The remaining ferrite powder is fed into the melt and mixed for 4 minutes. The torque at 4 minutes is 1126 mg and the temperature is 336°C. At the end of the run, the torque rheometer is stopped and disassembled to remove the melt of the composite material in teaspoon-sized pieces (also known as stones), and it is cooled.

[0073] The 25 square inch platens of a Carver hydraulic laboratory press were electrically heated to 310°C. A volume of composite stone was placed in the cavity of a metal mold. When the platens reached temperature, the mold was inserted into the press and allowed to heat at minimum pressure for 1 minute to 2 minutes, and then a pressure of 10,000 pounds per square inch (psi) was applied to the press ram for complete compaction. The mold was maintained under pressure for 1 minute to 2 minutes, and then the heat was turned off and cooling air was circulated through the platens. When the platen temperature was below 30°C, the pressure on the ram was released. The mold was removed from the press and the part was removed from the mold and then cut into rings for electromagnetic measurements.

[0074]

[0075] Table 2 shows that the specific magnetic loss (μ" / μ'2) of Example 6 at 1.2 GHz is 0.024, while Examples 7 and 8 have significantly lower specific magnetic loss values ​​of 0.020 and 0.018, respectively. This characteristic is manifested at frequencies of 1 GHz to 1.6 GHz.

[0076] Examples 9 to 11: Effect of Nickel on the Magnetic Properties of Co2Y Ferrites in PTFE

[0077] Prior to incorporating the ferrite powder into PTFE, the powder was pretreated with a 3:1 mixture by weight of an aromatic alkoxysilane (phenyl-trimethoxysilane) and a fluorinated aliphatic alkoxysilane ((tridecafluoro-1,1,2,2-tetrahydrooctyl)triethoxysilane). The silane was applied at a level of 2.0 weight percent (wt%) based on the total weight of the ferrite powder. For each sample, the silane treatment was applied to approximately 300 grams of ferrite and mixed in a Flaktek Speedmixer at 2,500 rpm for 15 seconds. The sample jar was removed from the mixing and scraped with a spatula and mixed again at 2,500 rpm for another 15 seconds. The samples were cured in an oven at 500°F (260°C) for five hours.

[0078] PTFE composite samples were prepared using DYNEON 2029Z PTFE fine powder resin. For a 45 volume percent loading, 66.9 wt % treated filler was blended with 33.1 wt % PTFE powder (based on dry solids) and mixed on a Flaktek mixer at 2,500 rpm for 15 seconds. The tank was removed and 21 wt % dipropylene glycol (DPG) based on the total mixed weight was added and stirred with a spatula. The lubricated crumbs were mixed on the Flaktek at 2,500 rpm for 15 seconds, removed, stirred with a spatula, and mixed again on the Flaktek under the same conditions.

[0079] The lubricated chips were pressed in a 7 cm x 7 cm rectangular three-part die to form a 7 cm x 7 cm x about 7 mm billet. The billet was calendered on a FARRELL laboratory calender with a roller heated to 50°C to form a sheet of about 0.7 mm. The sheet was soaked in warm water to remove the DPG lubricant and baked at 500°F (260°C) for 16 hours.

[0080] The dried sheets were trimmed to 7 cm x 7 cm and placed in a three-part mold. The sheets were laminated together in the mold using a 6 inch x 6 inch (15.2 cm x 16.2 cm) laboratory CARVER press at 345°C at a total force of 7,500 pounds per square inch (51.7 megapascals (MPa)) and a 45 minute soak time.

[0081]

[0082] Table 3 shows that Co2Y-type ferrite maintains low specific magnetic loss (0.013 to 0.03) within the frequency range of 1 GHz to 2 GHz.

[0083] Example 3: Co2Y type ferrite

[0084] Co2Y ferrite particles were prepared according to Example 1 to obtain the ferrite of Formulation II. Co2Y ferrite powder was mixed with a 10 wt% poly(vinyl alcohol) solution and then sieved through a 40# sieve to form pellets. The pellets were pressed into annular bodies at 1,800 pounds, and the green bodies were sintered at 1,200°C for two hours in a tube furnace in which oxygen flowed at a rate of 0.5 liters / minute. The sintered annular bodies had the following dimensions: an outer diameter of 7 millimeters (mm), an inner diameter of 3 mm, and a height of 3 mm to 4 mm. The relative density of the porous ceramic was about 78%.

[0085] The magneto-dielectric properties of the samples were determined within a frequency range of 0.1 GHz to 18 GHz, and the results are shown in Table 4.

[0086]

[0087] The data show that Co2Y ferrite has a very low magnetic loss of less than or equal to 0.09 at 1.2 GHz while maintaining a magnetic permeability greater than 3. In addition, Co2Y ferrite has a dielectric constant of less than 9 at 1.2 GHz while maintaining a low dielectric loss of less than or equal to 0.006. The data also show that Co2Y ferrite has a very low magnetic loss of less than or equal to 0.15 at 1.6 GHz while maintaining a magnetic permeability greater than 3. In addition, Co2Y ferrite has a dielectric constant of less than 9 at 1.6 GHz while maintaining a low dielectric loss of less than or equal to 0.008.

[0088] Compositions, methods and articles may alternatively comprise, consist of, or consist essentially of any suitable material, step or component disclosed herein, any suitable material, step or component disclosed herein. Compositions, methods and articles may additionally or alternatively be expressed as being free of or essentially free of any material (or substance), step or component that is not otherwise required to achieve the function or purpose of the composition, method and article.

[0089] As used herein, "a", "an", "the", and "at least one of..." do not indicate a limitation of quantity, and are intended to encompass both the singular and the plural, unless the context clearly indicates otherwise. For example, "element" has the same meaning as "at least one element", unless the context clearly indicates otherwise. The term "combination" includes blends, mixtures, alloys, reaction products, and the like. In addition, "at least one of..." means that the list includes each element independently, as well as combinations of two or more elements in the list, and combinations of at least one element in the list with similar elements not listed.

[0090] Unless otherwise clearly indicated by the context, the term "or" means "and / or". References throughout the specification to "one aspect", "another aspect", "some aspects", etc. mean that a particular element (e.g., feature, structure, step, or characteristic) described in conjunction with the aspect is included in at least one aspect described herein, and may or may not be present in other aspects. In addition, it should be understood that the described elements may be combined in any suitable manner in the various aspects.

[0091] Unless specified to the contrary herein, all test standards are the most recent standards in effect prior to the filing date of the present application (or, if priority is claimed, the filing date of the earliest priority application in which the test standard appears).

[0092] The endpoints of all ranges involving the same component or characteristic are inclusive of the endpoints, independently combinable, and include all intermediate points and ranges. For example, the range of "up to 25 wt %, or 5 wt % to 20 wt %" includes the endpoints and all intermediate values ​​of the range of "5 wt % to 25 wt %, such as 10 wt % to 23 wt %, etc.

[0093] Unless defined otherwise, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs.

[0094] All cited patents, patent applications, and other references are incorporated herein by reference in their entirety. However, if a term in the present application contradicts or conflicts with a term in the incorporated reference, the term from the present application takes precedence over the conflicting term from the incorporated reference.

[0095] Although specific embodiments have been described, the applicant or other persons skilled in the art may conceive of alternatives, modifications, variations, improvements, and substantial equivalents that are not currently foreseen or may not be foreseen. Therefore, the appended claims, as filed and as may be amended, are intended to cover all such alternatives, modifications, variations, improvements, and substantial equivalents.

Claims

1. A Co2Y ferrite comprising: oxides of at least Ba, La, Co, Me, Fe and optionally Ca; wherein Me is at least Ni and optionally one or more of Zn, Cu, Mn or Mg.

2. The Co2Y type ferrite according to claim 1, wherein the Co2Y type ferrite has a formula Ba 1- x La x Ca n Co 2-y-z Me y Fe 12-m O 22 , wherein x is 0.01 to 0.5, or 0.1 to 0.5; y is 0.01 to 1.5, or 0.1 to 1, or 0.2 to 0.5; z is -0.5 to 0.5, or -0.2 to 0; and m is -2 to 2, or 0.1 to 0.5; n is 0 to 0.5, or 0.01 to 0.

5.

3. The Co2Y type ferrite according to claim 2, wherein the Co2Y type ferrite has a formula Ba 1- x La x Ca n Co 2-y-z Ni y Fe 12-m O 22 .

4. The Co2Y ferrite according to any one of the preceding claims, wherein D of the Co2Y ferrite 50 The particle size is 2 microns to 10 microns.

5. The Co2Y ferrite according to any one of the preceding claims, wherein the porosity of the Co2Y ferrite is 0 volume percent to 50 volume percent, or 20 volume percent to 45 volume percent based on the total volume of the Co2Y ferrite.

6. The Co2Y ferrite according to any one of the preceding claims, wherein the magnetic permeability of the Co2Y ferrite in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz is greater than or equal to 3, or is 3 to 6, or 3 to 4.

7. The Co2Y ferrite according to any one of the preceding claims, wherein the magnetic loss of the Co2Y ferrite in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz is less than or equal to 0.75, or less than or equal to 0.5, or less than or equal to 0.09, or is 0.07 to 0.

2.

8. The Co2Y ferrite according to any one of the preceding claims, wherein the dielectric constant of the Co2Y ferrite is less than or equal to 9, or is 8 to 9 in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz.

9. The Co2Y ferrite according to any one of the preceding claims, wherein the dielectric loss of the Co2Y ferrite in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz is less than or equal to 0.01, or is 0.002 to 0.

009.

10. A composite material comprising a polymer and a Co2Y-type ferrite according to any one of the preceding claims.

11. The composite material of claim 10, wherein the polymer comprises at least one of paraffin wax, polytetrafluoroethylene, polyethylene, polypropylene, polyolefin, polyurethane, silicone polymer, liquid crystal polymer, poly(ether ether ketone) or poly(phenylene sulfide).

12. The composite material of any one of claims 10 to 11, wherein the polymer comprises polytetrafluoroethylene or poly(phenylene sulfide).

13. The composite material according to any one of claims 10 to 12, wherein the composite material has at least one of the following: A magnetic permeability greater than or equal to 1.5, or between 1.5 and 4, or between 1.5 and 2 in the frequency range of 1 GHz to 2 GHz, or at 1.2 GHz; A specific magnetic loss of less than or equal to 0.02, or less than or equal to 0.03, or less than or equal to 0.015, or between 0.012 and 0.03 in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz; A dielectric constant of less than or equal to 6.5, or between 5 and 6.5, in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz; or Dielectric loss of less than or equal to 0.008, or less than or equal to 0.006, or between 0.002 and 0.006 in the frequency range of 1 GHz to 2 GHz or at 1.2 GHz.

14. The composite material according to any one of claims 10 to 13, wherein the composite material comprises 5 volume percent to 95 volume percent, or 50 volume percent to 80 volume percent, or 40 volume percent to 60 volume percent of the Co2Y-type ferrite based on the total volume of the composite material.

15. The composite material according to any one of claims 10 to 14, wherein the porosity of the composite material is 0 volume percent to 45 volume percent, or 15 volume percent to 35 volume percent, based on the total volume of the composite material.

16. An article comprising the ferrite composition according to any one of claims 1 to 9 or the composite material according to any one of claims 10 to 15.

17. The article of claim 16, wherein the article is an antenna.

18. A method of manufacturing a Co2Y-type ferrite (optionally according to any one of claims 1 to 9), comprising: milling a ferrite precursor compound comprising oxides of at least Ba, La, Co, Me and Fe to form a magnetic oxide mixture, wherein Me comprises Ni and optionally an additional divalent element such as one or more of Zn, Cu, Mn or Mg; as well as The magnetic oxide mixture is calcined in an oxygen or air atmosphere to form the Co2Y-type ferrite.

19. The method of claim 18, wherein the calcining of the mixed ferrite is performed at a calcination temperature of 800°C to 1,300°C, or 900°C to 1,250°C, or a calcination time of 0.5 hours to 20 hours, or 1 hour to 10 hours.

20. The method of any one of claims 18 to 19, further comprising forming a composite material comprising the Co2Y-type ferrite and a polymer.

Citation Information

Patent Citations

  • Silylation process

    US4518787A

  • Surface treatment agents and polymers comprising substituted phenyl silanes and siloxanes

    US4756971A

  • Particulate filled composite film and method of making same

    US5506049A